Literature Review: The Effectiveness First Aid Pressure Immobilization Bandages Technique of Snake Bite - Dian Nopita; Ridlwan Kamaluddin (Program Studi Keperawatan Blora, Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
Backgrounds: Snake bites are a medical emergency that can cause permanent disability and even death (Wintoko and Prameswari 2020). The main principle recommended for the first treatment of a snakebite is to immobilize the area with a pressure bandage (pressure immobilization bandages) then immediately referred to the hospital for further treatment.Objective: To know the effectiveness of pressure immobilization bandages (PIB) first aid against snake bite.Methods: Article searches were conducted electronically using Google Scholar, PubMed, Science direct, National Library and Pro quest databases. Articles used from 2016 to 2021. The keywords in this article search were “pressure immobilization bandages” and “snake bite. So that 5 research articles were reviewed. Inclusion criteria included articles published in 2016-2021, articles in Indonesian and English, involving snake bite patients and being given the Pressure immobilization bandage technique intervention. Meanwhile, the exclusion criteria include articles that cannot be accessed, based on meta-analysis, and journals that discuss snake bites but are not in accordance with the topic to be reviewed.Results: Pressure immobilization bandages (PIB) can be used in first aid because they can inhibit the spread of snake venom and are 20 times faster in the healing process if done in first aid.Conclusion: Pressure immobilization bandages (PIB) are effective in first aid for snake bites.Keywords: Pressure immobilization bandages; snake bite